New species of Elaphidiini (Coleoptera, Cerambycidae, Cerambycinae) from Mexico and Central America, and new records in Cerambycidae and Disteniidae - Heffern, Daniel; Santos-Silva, Antonio (Zootaxa, 2025)
Five new species are described in Elaphidiini: Aneflomorpha spinifera sp. nov., from Mexico (Jalisco); Aneflomorpha makra sp. nov., from Mexico (Oaxaca); Aneflomorpha guatemalana sp. nov., from Guatemala; Aneflomorpha gracilenta sp. nov., from Mexico (Oaxaca); and Aneflus macraei sp. nov., from Mexico (Oaxaca). Additionally, new records are provided for: Susuacanga marcelae Botero, 2015 (Cerambycidae, Cerambycinae, Eburiini), with the female illustrated for the first time; Ameriphoderes cribricollis (Bates, 1892) (Cerambycidae, Cerambycinae, Rhinotragini); Spinestoloides hefferni Santos-Silva, Wappes & Galileo, 2018 (Cerambycidae, Lamiinae, Desmiphorini), with the male illustrated for the first time; and Novantinoe solisi Santos-Silva & Hovore, 2007 (Disteniidae, Disteniinae).